Genotypic variability in stress responses of Sorghum bicolor under drought and salinity conditions - Alzahrani, Yahya; Abdulbaki, Abdulbaki Shehu; Alsamadany, Hameed (Frontiers in Genetics, 2025)
IntroductionSorghum bicolor: widely cultivated in Asia and Africa, faces increasing challenges from climate change, specifically from abiotic stresses like drought and salinity. This study evaluates how different sorghum genotypes respond to separate and combined stresses of drought and salinity.MethodsCarried out with three replications using a randomized complete block design, the experiment measured biochemical and physiological parameters, including stomatal conductance, chlorophyll content, and antioxidant enzyme activities. Molecular analysis focused on stress-responsive gene expression.ResultsResults indicated enhanced stress responses under combined conditions, with significant variation in antioxidant enzymatic activities among genotypes. Genotype-specific osmotic adjustments were observed through proline and glycine betaine accumulation. Physiological parameters such as chlorophyll content, cell membrane stability, stomatal conductance, and water potential were critical indicators of stress tolerance. Gene expression analysis revealed upregulation of stress-responsive genes, particularly under combined stress conditions.DiscussionCorrelation and principal component analysis analyses highlighted the interdependencies among traits, emphasizing their roles in oxidative stress mitigation. Samsorg-17 exhibited the highest resilience due to consistently high levels of catalase, superoxide dismutase, and glycine betaine, alongside superior physiological attributes. CRS-01 showed moderate resilience with the highest Na/K ratio and notable photosynthesis rate and relative water content, but was less consistent in biochemical markers under stress. Samsorg-42 demonstrated resilience under specific conditions but was generally less robust than Samsorg-17 across most indicators. These findings emphasize the importance of developing stress-resilient sorghum cultivars through targeted breeding programs to enhance tolerance to drought and salinity in sustainable agriculture.